New Paradigms in Banking, Financial Markets and Regulation? - Morten Balling; Frank Lierman; Freddy Van den Spiegel; Rym Ayadi; David T. Llewellyn; Martin Merlin; Donato Masciandaro; Marc Quintyn; Rosaria Vega-Pansini; Adam Szyszka; Rym Ayadi; Frank de Jonghe; et al. (SUERF - The European Money and Finance Forum, 2012)
On May 11-12, 2011, SUERF, the Belgian Financial Forum, the Brussels Finance Institute and the Centre for European Policy Studies (CEPS) jointly organised the 29th SUERF Colloquium New paradigms in money and finance? The papers included in this SUERF Study are based on contributions to the Colloquium. The 2008-11 financial crisis has demonstrated unsatisfactory performance in financial institutions and in financial regulation and supervision all over the world. The contributors to the present volume look with critical eyes on financial theories, supervisory structures, (mis)pricing of risk and distorted incentives, risk management models and procedures, conflicts of interest and bank strategies. Their perspectives are quite different, but they share the ambition of finding improved analytical, organizational or managerial approaches so that decisionmakers have a better chance of showing good performance in the future. In essence, they are looking for new paradigms in banking, financial markets and regulation.
Keywords: F36; G1; G2; G18; G21; G22; G28; G30; G32; G33; G34; L1; L25; P13; 330; Basel III; financial supervision; macroprudential supervision; regulatory framework; transformation of financial markets; neoclassical economics; behavioural finance; financial crisis; cooperative banks; banking; corporate governance; performance; stability; diversity; deposit insurance; risk-based premium; covered deposits; expected loss; option pricing; competition; concentration; market structure; Finanzkrise; Marktversagen; Bankenkrise; Basler Akkord; Finanzmarktregulierung; Europa